AMERICAN SOCIETY AT THE BEGINNING OF THE XX CENTURY AND ITS IMPACT TO THE NATIONAL LITERATURE - Ziyodillaeva Makhbuba Ermatovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: XX century is known with two great wars and their tremendous effect to the social and cultural life of many countries. Indeed, America is also considered to be one of the countries with much harm in its economy, culture as well as its literature. The following article depicts socio-cultural life in XX century America and several prominent literary man during this period.